2017
DOI: 10.1097/bpo.0000000000000584
|View full text |Cite
|
Sign up to set email alerts
|

Repositioning of the Annular Ligament in the Management of Missed Monteggia Fracture

Abstract: Level IV-therapeutic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 11 publications
2
38
0
Order By: Relevance
“…These authors operated on select patients with missed Monteggia fracture using open reduction only, reporting good results. Among them, one report recommended that open reduction with repositioning or repair of the annular ligament might be a favorable option 26. In our study, we achieved stable reduction of the radial head with open reduction alone in five patients.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…These authors operated on select patients with missed Monteggia fracture using open reduction only, reporting good results. Among them, one report recommended that open reduction with repositioning or repair of the annular ligament might be a favorable option 26. In our study, we achieved stable reduction of the radial head with open reduction alone in five patients.…”
Section: Discussionsupporting
confidence: 52%
“…Open reduction alone is not sufficient to obtain and maintain reduction of the radial head in all patients with missed Monteggia fracture and has been used in only a few studies 1462526. These authors operated on select patients with missed Monteggia fracture using open reduction only, reporting good results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In study of Park et al, ulnar osteotomy and correction of the ulnar deformity are the key components to achieve reduction and this is also true in our study Another study showed both ulnar ostetomy and annular ligament reconstruction are required. 19 Another study shows good to excellent results in chronic Monteggia fractures if surgery performed before radial head is deformed. 20 Transcapitellar wire insertion is also debatable.…”
Section: Discussionmentioning
confidence: 98%
“…We used the Henry approach, as described in previous studies. 4 Once the muscles adjacent to the radiocapitellar joint had been cleared, the pseudocapsule surrounding the capsule was opened from the distal to the proximal region to expose the radial head. Then, we evaluated the state of the cartilage of the radial head.…”
Section: Surgical Techniquementioning
confidence: 99%